Islamic Values ​​in the Ulu Serawai Manuscript as Local Wisdom in Cultural Education in South Bengkulu - Fitri Novianti; Yeti Dewanti; Dedi Irama (Lembaga Penjaminan Mutu, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2026)
This research addresses the rapidly declining understanding of the Ulu script and Islamic values among youth in South Bengkulu due to intense globalization and modernization. It aims to identify Islamic values embedded in the kayik beterang section of the Ulu Serawai manuscript, analyze how they reflect Serawai local wisdom, and examine their practical relevance for contemporary cultural education. Employing a qualitative descriptive-analytical approach, data were collected through observation, in-depth interviews, documentation, and systematic content analysis of manuscript MNB 07.18. Data validity was ensured through source, technique, and time triangulation, while analysis followed the Miles and Huberman interactive model. Findings reveal that the manuscript integrates core Islamic principles encompassing faith, worship, ethics, and social relations within indigenous customary practices. These values are manifested through monotheistic affirmations, ritual purification processes, moral conduct guidelines, and communal solidarity, demonstrating a harmonious synthesis between Islamic teachings and Serawai cultural identity. The study concludes that the manuscript functions not merely as a historical artifact but as a dynamic medium for character and cultural education. Its contextual integration into modern curricula can foster a generation that is religiously grounded, ethically conscious, and culturally resilient. By preserving and actualizing these indigenous Islamic values, educators can effectively counter cultural erosion while strengthening local identity.